2019
DOI: 10.1002/ece3.5917
|View full text |Cite
|
Sign up to set email alerts
|

The underdog invader: Breeding system and colony genetic structure of the dark rover ant (Brachymyrmex patagonicus Mayr)

Abstract: Ants are among the most successful species at invading new environments. Their success undeniably comes from their various modes of reproduction and colony breeding structures, which influence their dispersal ability, reproductive potential, and foraging strategies. Almost all invasive ant species studied so far form supercolonies, a dense network of interconnected nests comprising numerous queens, without aggression toward non-nestmates. This strategy results in invasive colonies that are able to grow extreme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 117 publications
(171 reference statements)
2
14
0
Order By: Relevance
“…Most trails analyzed in this study exhibited a relatively high level of relatedness, indicating the occurrence of a single reproductive queen in most colonies. These findings confirm previous results that a majority of invasive colonies of B. patagonicus are monogyne (Eyer et al, 2020). This study also highlights the need for multiple tools to efficiently infer the colony boundaries in socially complex species (Ellis et al, 2017;Eyer et al, 2017;Reiner Brodetzki & Hefetz, 2018).…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…Most trails analyzed in this study exhibited a relatively high level of relatedness, indicating the occurrence of a single reproductive queen in most colonies. These findings confirm previous results that a majority of invasive colonies of B. patagonicus are monogyne (Eyer et al, 2020). This study also highlights the need for multiple tools to efficiently infer the colony boundaries in socially complex species (Ellis et al, 2017;Eyer et al, 2017;Reiner Brodetzki & Hefetz, 2018).…”
Section: Discussionsupporting
confidence: 91%
“…High relatedness values between workers sampled on a given trail would suggest that they belong to a single colony. Moderate relatedness values may denote the foraging trail of a single, yet more diverse, colony (e.g., polygyne), as Eyer et al (2020) found the relatedness within polygyne colonies ranged from 0.16 to 0.64. In contrast, relatedness values close to zero would indicate that workers from different colonies forage on a common trail.…”
Section: Genetic Procedures and Analysesmentioning
confidence: 99%
See 3 more Smart Citations